The effectiveness of anger management programme amongst children in conflict with the law at Mankweng, Capricorn District, Limpopo Province - Mogano, Thapelo Isaac (My University, 2022)
Anger Management is now a major issue affecting children and youth across societies. It often leads children and youth to criminal offences. Despite attending the anger management programme, children and youth still fail to control their emotions. There are various factors that lead them unable to control their anger-triggering situations and ultimately re-offend. Some do so because they did not benefit from the programme. There are few studies, particularly within the anger management programmes tailored for children and youth in South Africa. This study aimed at exploring the anger management programme. The study argues that the anger management programme has an influence on the re-offending behaviour of children and youth who have gone through the programme. The study focused in Limpopo Province using Mankweng area as a case. Behaviour Modification, Social Learning and Strain were used as theories to evaluate the effectiveness of the anger management programme amongst children in conflict with the law. The study applied the qualitative approach, with the exploratory case study design. Purposive and convenient sampling techniques were used to select thirteen (13) respondents, wherein ten (10) were youth who have gone through the anger management programme while they were still children, and three (3) social workers who facilitate the programme at NICRO in Mankweng. Data was collected through semi-structured interviews, guided by an interview schedule with open-ended questions. The Nvivo software was used to organise and manage the data, and Creswell’s steps of data analysis were used to thematically analyse the data. The findings of this study indicate that lack of anger management skills amongst children increases the likelihood of juvenile delinquency. These children act aggressively and violently when faced with anger-triggering situations. The study further revealed that peer-relationship, poor parenting skills, family background, lack of support, abusive parents and strenuous predicaments are factors that affect children and youth to manage their anger, leading to re-offending. Despite attending the anger management programme, these factors still pushed children and youth into committing criminal offences again. This study unearthed that the competency of the anger management programme facilitators equally plays an important role in recidivism. It helps children to benefit from ways of dealing with anger and avoid being aggressive and violent. The study further viii revealed that most youth participants in the study understood what the programme seeks to address and achieve. Participants benefitted from the programme, and it was easy for them to learn about anger management, and never reoffended. The study concluded that children who lack anger management skills are likely to commit criminal offences again. Factors such peer-relationship, poor parenting skills and strenuous predicaments affect the ability of children and youth to manage anger emotions. It was further concluded that abusive parents, family background and lack of support also cause the reoffending behaviour amongst children and youth. Facilitators’ competency and children’s challenges in understanding the programme affect the impact of the programme to prevent criminal behaviour. The study recommended proper assessments of children’s circumstances, involvement of peers and parents, training of social workers who offer the anger management programme and supplementary programmes to support the programme.
Thesis (M.A. (Social Work)) -- University of Limpopo, 2022
Keywords: Anger management; Children offenders; Behaviour modification; Juvenile delinquency; Anger in children; Juvenile delinquency; Youth -- Crimes against; Youth -- Crimes against -- South Africa -- Limpopo